2011
DOI: 10.1111/j.1365-2648.2011.05631.x
|View full text |Cite
|
Sign up to set email alerts
|

Key characteristics of knowledge transfer and exchange in healthcare: integrative literature review

Abstract: Aim: This paper presents the results of a review of literature relating to knowledge transfer and exchange in healthcare. Background: Treatment, planning and policy decisions in contemporary nursing and healthcare should be based on sound evidence wherever possible, but research knowledge remains generally underused. Knowledge transfer and exchange initiatives aim to facilitate the accessibility, application and production of evidence and may provide solutions to this challenge. This review was conducted to he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
125
2
10

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(139 citation statements)
references
References 47 publications
2
125
2
10
Order By: Relevance
“…Other authors have reached similar conclusions. [35][36][37] However, the act of researching, collating and exchanging knowledge is a way of gaining or preserving power by different groups. The present study found that the ability of some stakeholders to engage in KT/E is constrained by a range of factors, particularly conflicting priorities, lack of funding and a limited culture of knowledge-sharing.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors have reached similar conclusions. [35][36][37] However, the act of researching, collating and exchanging knowledge is a way of gaining or preserving power by different groups. The present study found that the ability of some stakeholders to engage in KT/E is constrained by a range of factors, particularly conflicting priorities, lack of funding and a limited culture of knowledge-sharing.…”
Section: Discussionmentioning
confidence: 99%
“…This is an important finding in conjunction with the finding that the overwhelming majority of respondents expressed a desire for training in this area, as positive attitudes have been identified as a key determinant in the successful implementation of evidence based interventions (Pentland et al, 2011; Varnell, Haas, Duke, & Hudson, 2008), such as trauma-informed care.…”
Section: Discussionmentioning
confidence: 71%
“…These strategies obviously do not guarantee that research will have an influence on policy or practice, nonetheless KT has been broadly viewed as a major advance toward this goal because it encourages greater intentionality on the part of the research community in establishing appropriate preconditions (e.g., relevance, accessibility, actionability, and stakeholder capacity to use research) to support research uptake. 8 At least on the surface, therefore, KT appears to offer very promising strategies for accelerating the uptake of research evidence to practically reduce urban health inequities. However, most KT models and best practices have been generated primarily for clinical and single-sector health care decision-making contexts and are rooted in evidence-based medicine.…”
Section: Introductionmentioning
confidence: 99%